2020
DOI: 10.1084/jem.20191561
|View full text |Cite
|
Sign up to set email alerts
|

A loss-of-function NUAK2 mutation in humans causes anencephaly due to impaired Hippo-YAP signaling

Abstract: Failure of neural tube closure during embryonic development can result in anencephaly, one of the most common birth defects in humans. A family with recurrent anencephalic fetuses was investigated to understand its etiology and pathogenesis. Exome sequencing revealed a recessive germline 21-bp in-frame deletion in NUAK2 segregating with the disease. In vitro kinase assays demonstrated that the 7–amino acid truncation in NUAK2, a serine/threonine kinase, completely abrogated its catalytic activity. Patient-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…NUAK2 is a serine/threonine kinase, belonging to the family of AMPK, whose mutations are associated to congenital severe neurodevelopmental defects [ 71 ], although it is rarely observed mutated in cancer (Fig. 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…NUAK2 is a serine/threonine kinase, belonging to the family of AMPK, whose mutations are associated to congenital severe neurodevelopmental defects [ 71 ], although it is rarely observed mutated in cancer (Fig. 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in YAP1 also leads to congenital malformations during human brain development like orofacial clefting and intellectual disabilities (Williamson et al., 2014). A recent study investigating the significance of Hippo signaling during Drosophila brain development has illustrated that loss of Sd, a core member of Hippo pathway, can also lead to developmental deformities in the brain by virtue of abnormal neural expansion, as exemplified by their reduced cognitive performance (Bonnard et al., 2020). Reduced activity of Hippo components like Tead2 and PP2AC α has been implicated in mammalian neural tube defects and cerebral atrophy, respectively (Kaneko et al., 2007; Yu et al., 2016).…”
Section: Hippo/yap Signaling In Neurodevelopmental and Neurodegeneratmentioning
confidence: 99%
“…Periventricular nodular heterotopia is a form of cortical malformation which is frequently reported to be a consequence of insufficiency in several Hippo pathway‐associated genes like FILAMIN A, FAT4, DCHS1, and MOB2 (Cappello et al., 2013; Fox et al., 1998; O'Neill et al., 2018). A recent study has shown that loss‐of‐functional mutation in NUAK2 leads to reduced Hippo signaling via cytoplasmic YAP retention, which is turn results in anencephaly, one of the most common birth defects in humans arising from failure of neural tube closure during embryonic development (Bonnard et al., 2020). In the absence of NF2, there is an elevated YAP1 activity in the NPCs, which disrupt the formation of guidepost cells and results in dysplasia of the corpus callosum (Lavado et al., 2014).…”
Section: Hippo/yap Signaling In Neurodevelopmental and Neurodegeneratmentioning
confidence: 99%
“…NUAK1 has also been shown to be able to phosphorylate LATS1 [24], but whether NUAK1 exerts a similar or opposing function to NUAK2 on Hippo pathway signaling remains elusive. Recently, NUAK2 and the Hippo system have been shown to be of high relevance to a crucial stage in development of the human central nervous system: namely, the closing of the neural tube during embryogenesis [47]. Defects in closing the neural tube lead to a developmental brain defect called anencephaly: the absence of a large portion of the brain.…”
Section: Additional Dynamics Of Nuak Kinase Functionmentioning
confidence: 99%